Rwanda Nutrition, Markets and Gender Analysis 2015: An integrated approach towards alleviating malnutrition among vulnerable populations in Rwanda - Lung'aho, Mercy G.; Birachi, Eliud Abucheli; Butare, L.; Musoni, Augustine; Muhinda M, JJ; Buruchara, Robin Arani (Guvernment of Rwanda, 2015)
The Nutrition, Markets and Gender (NMG) Survey was conducted in Rwanda to investigate the causes of malnutrition in children under 24 months. The NMG Survey was informed by the 2010 Demographic Health Survey (DHS) for Rwanda that gave some insight into the knowledge and trend of malnutrition in the country for the period 2005 to 2010. The DHS results indicated a 6 percent decline in stunting among children under the age of five years. The key findings from the 2014/2015 DHS that followed the same delineation as the DHS 2010 provided the most current status of malnutrition in Rwanda and showed further overall improvements in child growth outcomes with 37.9 percent of children under five years classified as stunted. These results again indicated a 6.3 percent decline in stunting among children under the age of five years for the period 2010 to 2015. This progressive trend is a testament to the country’s commitments to prioritise nutrition issues and nutrition programmes in its development agenda. The Government of Rwanda, through the Ministry of Health, has prioritised malaria control, nutrition education, and better public healthcare. However, in spite of the advancements made, the consensus is that high rates of chronic malnutrition among children still prevail. Thus a better understanding of risk factors that contribute to child malnutrition at the household level in Rwanda was needed to strengthen the fight against malnutrition in the country. The ‘Comprehensive Food Security and Vulnerability and Nutrition Analysis’ – CFSVA 2012 – report produced by the Ministry of Agriculture and Animal Resources (MINAGRI), the National Institute of Statistics of Rwanda (NISR) and the World Food Programme (WFP) acknowledged that vulnerable households are increasingly reliant on markets as a source of food; providing on average 65 percent of the food consumed by a household. It is therefore clear that household nutrition outcomes in such households are dependent on markets. In addition, it is widely accepted that gender dynamics influence decision-making in the household. Thus gender dynamics affect decisions related to food, care, markets, and health. Therefore this survey focused on nutrition, markets, and gender to determine the factors that influence the nutrition status of children under 24 months. Moreover, a disconnect between agricultural production and nutrition outcomes was revealed in the CFSVA 2012 report that indicated that the northern agricultural zones, considered the bread basket of the country, had stunting rates of up to 66 percent in children under 60 months.